Domestic heating from forest logging residues: environmental risks and benefits. (15th July 2015) - Giuntoli, J.; Caserini, S.; Marelli, L.; Baxter, D.; Agostini, A.
Abstract: The European Union (EU) relies largely on bioenergy to achieve its climate and energy targets for 2020 and beyond. Special focus is placed on utilization of biomass residues, which are considered to cause low environmental impacts. We used the dataset from the latest European Commission document on the sustainability of solid and gaseous biomass (SWD2014 259), complementing those results by: i) designing three pathways for domestic-heat production using forest logging residues, with different combustion technologies; ii) expanding the analysis to include forest carbon stock development with and without bioenergy; iii) using absolute climate metrics to assess the surface temperature response by the end of the century to a bioenergy and a reference fossil system; iv) including multiple climate forcers (well-mixed GHG, near term climate forcers and surface albedo change); iv) quantifying life cycle impacts on acidification, particulate matter emissions and photochemical ozone formation; v) reviewing potential risks for forest ecosystem degradation due to increased removal of residues. Supply-chain GHG savings of the three pathways analysed ranged between 80% and 96% compared to a natural gas system, above the 70% threshold suggested by the EU. However, the climate impact of bioenergy should be assessed by considering also the non-bioenergy uses of the biomass and by including all climate forcers. We calculate the Surface Temperature Response to bioenergy and fossil systems by means of Absolute Global surface Temperature Potential (AGTP) metric. Domestic heating from logging residues is generally beneficial to mitigate the surface temperature increase by 2100 compared to the use of natural gas and other fossil sources. As long as residues with a decay rate in the forest higher than 2.7%*yr −1 are considered as feedstock, investing now in the mobilization of residues for heat production can reduce the temperature increase by 2100 compared to all the fossil sources analysed, both in case of bioenergy as a systemic change or in case of bioenergy as a transitory option. Furthermore, several environmental risks are associated with the removal and use of forest logging residues for bioenergy. These issues concern mostly local air pollution, biodiversity loss and, mainly for stumps removal, physical damage to forest soils. Forest logging residues are not free of environmental risks. Actions promoting their use should consider: (i) that climate change mitigation depends mainly on the decay rate of biomass under natural decomposition and time and rate of technology deployment, (ii) whether management guidelines aimed at protecting long-term forest productivity are in place and (iii) whether proper actions for the management of adverse effects on local air pollution are in place. Highlights: Supply-chain GHG emissions savings compared to natural gas above 80% for all pathways. Climate impact of heat from logging residues is mostly caused by well-mixed GHG. Heat from residues with a decay rate higher than 2.7%*yr −1 causes lower temperature increase than natural gas by 2100. Actions for mitigation of adverse impacts on local air pollution should be in place. Harvesting guidelines should be implemented to protect long-term forest productivity.